Evolution of enrollments in special education in kindergarten, elementary and high school between 2009 and 2020 in Brazil (Research, Society and Development, 2022)
Discussing the inclusion of students with disabilities in the school environment implies bringing up very broad issues, such as: little investment in the Brazilian educational system; the lack of infrastructure in terms of physical resources to serve all students, whether special or not; the prejudice; discrimination; and the lack of credibility that still prevails in relation to different people, especially those with some kind of disability. These people are disrespected and are not understood as human beings with potential and capable of producing like other citizens. This article aims to investigate the evolution of special education enrollments in early childhood education and primary and secondary education from 2009 to 2020 in Brazil. A qualitative approach was used, using bibliographical research. For the development of this study, the 2020 School Census published by the National Institute of Educational Studies and Research Anísio Teixeira and the Directorate of Educational Statistics were used as data collection sources. In the years 2009 to 2020, the enrollment of special students in the common class followed a growing line in basic education, elementary and secondary education. This growth is related to the implementation of public education policies and adequate teacher training. These data show the importance of a serious public policy that fights for the inclusion of students with some type of disability to be placed within a common class.